Plasma levels of C-reactive protein and Interleukin-6 as markers of inflammation in patients with operative treated fractures - Hristijan Kostov; Elena Kostova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2024)
Conditions that affect plasma concentrations of acute-phase proteins include infections, trauma, surgical treatment, burns, tissue ischemia (infarctions), various immunological inflammatory conditions and cancer. The cytokine Interleukin-6 (IL-6) is the main stimulator for the production of numerous acute-phase proteins. It has been established that the induction of C-reactive protein (CRP) and production of serum amyloid A is caused by the cytokines IL-6 and IL-1 or TNF-alpha. Elevated levels of IL-6 during acute injuries or stress are often used as an indicator of systemic inflammation and are predictors of preoperative morbidity. We undertook this prospective randomized study in 90 patients undergoing surgery procedure after high-energy trauma, low-energy trauma and open fracture to define plasma levels of IL-6 and CRP over a 2-week period. We presented our results at seven time points, namely 6 hours pre-operatively and post-operatively in 2, 4, 5, 7 and 14 days respectively. We have attempted to find out whether IL-6 and CRP levels returned to baseline during this study period. In our study, we determined the influence of the examined parameters CRP and IL-6 in plasma on the early detection of surgical postoperative inflammation in operatively treated fractures. With the obtained results of our examined parameters, we can state that is provided a place for the routine procedure of CRP and IL-6 as predictors of possible postoperative inflammation.